The assurance of faith conscience in the theology of Martin Luther and John Calvin - Zachman, Randall C. 1953- (Minneapolis, MN Fortress, 1993)
Includes bibliographical references and index.
Keywords: Luther, Martin -- 1483-1546; Calvin, Jean, -- 1509-1564; Conscience -- religions aspects -- Christianity -- history of doctrines -- 16th century; Assurance (theology) -- history of doctrines -- 16th century